Microbiology in action - Heritage, J.; Evans, E. G. V. (Emlyn Glyn Vaughn); Killington, R. A. (Cambridge, UK ; New York, NY, USA : Cambridge University Press, 1999)
"Microbes play an important role in our everyday lives. As agents of infectious disease they cause untold human misery, yet their beneficial activities are manifold, ranging from natural cycling of chemical elements through to the production of food, beverages and pharmaceuticals. In this introductory level text the authors provide a clear and accessible account of the interactions between microbes, the environment and other organisms, using examples of both benficial and adverse activities."--Back cover
In this introductory level text the authors provide a clear and accessible account of the interactions between microbes, their environment and other organisms, using examples of both beneficial and adverse activities. The microbiology of soil and of nutrient cycling. What habitats are provided by soil? How are microbes involved in nutrient cycling? How is carbon cycled? How is nitrogen cycled? How is sulphur cycled? Plant-microbe interactions. What are mycorrhizas? What symbioses do cyanobacteria form? What symbioses do other nitrogen-fixing bacteria form? From what infections do plants suffer? Fungi. Bacteria. Viruses. How are microbes used to control agricultural pests? The microbiology of drinking water. What are water-borne disease? Cholera. Enteric fever. Bacilliary dysentry. Water-borne campylobacter infections. Water-borne virus infections. Water-borne protozoal diseases. How is water examined to ensure that it is save to drink? How is water purified to ensure that it is safe to drink? How is sewage treated to make it safe? Microbial products. How did microbes contribute to the First World War effort? What role do microbes play in the oil industry and in mining? How are microbial enzymes exploited? How do microbes help in the diagnosis of disease and related applications? How do microbes contribute to the pharmaceutical industry? How do microbes contribute to food technology? Food microbiology. How do microbes affect food? How are fungi used as food? How are microbes involved in bread and alcohol production? How are fermented vegetables and meats produced? Sauerkraut. Dill pickles. Other fermented vegetable products. Fermentation of meats. Silage production. Fermented dairy products. What role do microbes have in food spoilage and preservation? How do microbes cause food spoilage? How can food be preserved? What causes food poisoning? Chemical contamination of food. Food poisoning associated with consumption of animal tissues. Food poisoning associated with the consumption of plant material. What are food-borne infections? Bacterial food poisoning. Bacterial intoxication. What food poisoning is associated with bacterial infection? What is the role of fungal toxins in food poisoning? What viruses cause food-borne illness? What are the pre-disposing factors in food poisoning incidents? The human commensal flora. What constitutes the resident and transient flora of humans? What constitutes the commensal flora of the human skin? What constitutes the commensal flora of the human alimentary tract? What constitutes the commensal flora of the human upper respiratory tract? What constitutes the commensal flora of the human genital tract? What is the role of the human commensal flora? What factors affect the human commensal flora? Do viruses form part of the human commensal flora? Microbial infections. How do microbes cause disease and how do we defend ourselves from infection? What are urinary tract infections? What causes urinary tract infections? What are the symptoms of urinary tract infections? How may the diagnostic laboratory assist in the diagnosis of urinary tract infections? What causes sexually transmissible diseases? Acquired immunodeficiency syndrome (AIDS). Syphillis. Gonorrhoea. Non-specific urethritis and other bacterial infections. Candidosis (thrush). Trichomoniasis. Genital herpes infections. Genital warts. Pubic lice and scabies. What causes infections of the central nervous system? What causes meningitis? What causes encephalitis? What is rabies? What is progressive multifocal leukoencephalopathy? What are poliomyelitis and chronic fatigue syndrome? What are transmissible spongiform encephalopathies? What causes brain abscesses? What is tetanus and how is it related to botulism? What causes infections of the circulatory system? What is plague? What cause septicaemia? What are the symptoms and consequences of septicaemia? How is septicaemia diagnosed in the diagnostic microbiology laboratory? What is endocarditis and how does it develop? What causes oral cavity and respiratory functions? What causes infections of the oral cavity? What causes dental caries? Periodontal disease. Actinomycosis. Oral thrush. Cold sores. Upper respiratory tract infections. Sore throats and glandular fever. Tonsillitis. Mumps. Diptheria. Acute epiglottitis. Middle ear infections. Lower respiratory tract infections. Chronic bronchitis. Pneumonia. Legionnaire's disease. Tuberculosis. Whooping cough. Aspergillosis. What causes gastrointestinal infections? Pseudomembranous colitis. How are faecal samples examined for pathogens? What viruses are associated with gastroenteritis? Hepatitis. Peritonitis. What causes infections of skin, bone and soft tissues? What bacteria cause skin and muscle infections? What viruses cause skin lesions? What causes eye infections? What animal-associated pathogens cause soft tissue infections? What infections affect bone and joints? What causes perinatal infections? What infection do fungi cause? How are mycoses diagnosed in the laboratory? How do we recognise clinically important bacteria? Gram-positive cocci. Gram-positive bacilli. Mycobacteria. Gram-negative cocci. Gram-negative bacilli. Chemotherapy and antibiotic resistance. What inhibits bacterial cell wall synthesis? Fosfomycin. Cycloserine. Bacitracin. Vancomycin. Beta-lactams. Isoniazad. Which antibacterial agents affect bacterial cell membrane function? Which antibacterial agents are inhibitors of nucleic acid metabolism? Sulphonamides and trimethoprim. Quinolones. Which antibacterial agents are inhibitors of RNA metabolism? Which antibacterial agents are inhibitors of protein synthesis? Aminoglycosides. Tetracyclines. Chloramphenicol. Macrolides. Fusidic acid. Mupirocin. What drugs act as antifugal agents? Polyene antibiotics. Azoles. Griseofulvin. Flucytosine. Allylamines and benzylamines. What drugs can be used to treat virus infections? Aciclovir and ganciclovir. Amantidine. Ribavirin. Zidovudine. What causes antibiotic resistance in bacteria?
"Published in association with the Institute of Biology."
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Microbiology; Microbiology; Microbiologie; microbiology; SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- Microbiology; Microbiology; Mikrobiologe; Microbiologie; Microbiology; Electronic books; Electronic books